2019
DOI: 10.1002/edn3.19
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing airborne environmental DNA: A comparison of extraction methods, primer type, and trap type on the ability to detect airborne eDNA from terrestrial plant communities

Abstract: Airborne environmental DNA (eDNA) research has typically focused on the detection of pollen from anemophilous terrestrial plant species; however, recent findings have expanded the definition of airborne eDNA to include a variety of eDNA sources, such as leaf and flower fragments. While methods for capturing pollen are well studied, there is less known about how to best analyze and capture more broadly defined bulk airborne eDNA samples. Therefore, this study aimed to identify efficient techniques for the extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 45 publications
(81 reference statements)
1
64
0
Order By: Relevance
“…Within each sampling location, three Big Spring Number Eight (BSNE) passive dust traps were deployed. Johnson et al (2019b) demonstrated that BSNE traps performed well compared to other passive dust traps. The BSNE traps (Figure 2) consisted of two triangular traps 0.914 and 0.406 m above the ground.…”
Section: Edna Collection Extraction and Amplificationmentioning
confidence: 92%
“…Within each sampling location, three Big Spring Number Eight (BSNE) passive dust traps were deployed. Johnson et al (2019b) demonstrated that BSNE traps performed well compared to other passive dust traps. The BSNE traps (Figure 2) consisted of two triangular traps 0.914 and 0.406 m above the ground.…”
Section: Edna Collection Extraction and Amplificationmentioning
confidence: 92%
“…Despite being an emerging new environmental monitoring technique, the enormous potential of eDNA application in biological monitoring has already been widely recognized and established [ 32 ]. Methods in eDNA research—particularly, sampling and handling of samples, DNA extraction, DNA half-life in aquatic, terrestrial and air samples, contamination, low abundance of DNA from higher organisms—have been extensively reviewed [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Therefore, herein we have not discussed these topics and related issues.…”
Section: Can Edna/erna Biomonitor the Exposome?mentioning
confidence: 99%
“…What is surprising is that no active attempts to collect terrestrial biodiversity from air have been reported, even though reviews on the current state and future direction of eDNA metabarcoding (e.g., Ruppert, Kline & Rahman, 2019 ) mention the next area of interest being airborne DNA mostly in the context of microbes, pollen, and fungi. Early PCR-based studies were used to identify pollen ( West et al, 2008 ; Longhi et al, 2009 ; Folloni et al, 2012 ; Mohanty, Buchheim & Levetin, 2017 ) and a small number of metabarcoding studies of airborne particles have identified anemophilous plants (e.g., Johnson, Cox & Barnes, 2019a ; Johnson, Cox & Barnes, 2019b ), pathogenic microbes ( Nicolaisen et al, 2017 ; Núñez et al, 2017 ) and allergenic pollen ( Kraaijeveld et al, 2015 ; Korpelainen & Pietilainen, 2017 ; Núñez et al, 2017 ; Leontidou et al, 2018 ; Brennan et al, 2019 ), with a focus on human and crop health ( Yoo et al, 2017 ). Similarly, Abrego et al (2018) successfully conducted a fungal biodiversity survey by DNA barcoding fungal spores across Finland, and biodiversity assessments of seasonal plant and fungal diversity have been demonstrated as viable ( Banchi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%